Interactomic and Pharmacological Insights on Human Sirt-1 - Sharma, Ankush; Gautam, Vasu K.; Costantini, Susan; Paladino, Antonella; Colonna, Giovanni (Frontiers in Pharmacology, 2012)
Sirtuin family, in humans as well as in all mammalia, is composed by seven different homologous proteins with NAD-dependent deacetylase/ADP-ribosyltransferase activity. Numerous studies have determined their cellular location and their biological functions. In particular, Sirt-1 is defined as a nuclear protein involved in the molecular mechanisms of inflammation and neurodegeneration through the de-acetylation of many different substrates (PGC-α, FOXOs, NFκB). However experimental data in mouse suggest both its cytoplasmatic presence and nucleo-cytoplasmic shuttling upon oxidative stress. Recently we have modeled the three-dimensional structure of human Sirt-1, and highlighted that it is composed by four different regions: N-terminal region, allosteric site, catalytic core and C-terminal region and underlined that the two terminal regions have high intrinsic disorder propensity. Since Sirt-1 is implicated in various diseases and cancers, many different papers report experimental studies related to its functional activators. The aim of this article is i) to present interactomic studies on human SIRT-1 to understand its most important functional relationships in the light of the gene-protein interactions that control major metabolic pathways and ii) to show how this protein binds some activator molecules in order to evidence structural determinants, physico-chemical features and those residues involved in the formation of complexes. It is believed that these data will be useful to synthesize new effectors through drug design approaches.